EFFECT OF BACTERIAL CURING AND BACTERIAL ADDITIVE ON CONCRETE PROPERTIES (Advances in Civil and Architectural Engineering, 2023)
In this study, calcium carbonate was formed on the surfaces and inner structure of concrete using the microbially induced carbonate precipitation method. Bacillus megaterium bacteria were supplemented into the curing water and concrete mixtures. Three types of concrete were tested: control concrete, bacteria-containing concrete, and concrete cured in bacterial liquid. Compressive strength, water absorption, capillary water absorption, scanning electron microscopy (SEM), and mapping analyses were conducted to investigate the effects of bacterial additive or bacterial curing to concrete specimens. Bacteria spore added to the concrete mixture and curing in bacterial media increased the compressive strengths of concrete by up to 9,52 % at the end of 28 days of curing. Bacterial curing and the addition of bacteria spores caused a reduction in water absorption rates owing to changes in the concrete structures. Calcite only formed on the surfaces of the samples treated with bacterial curing liquid, thereby limiting its effect on capillary water absorption. In contrast, capillary water absorption in the bacterial concrete decreased by 50 % compared to the control concrete. The crystalline structures of calcium carbonate and bacterial concrete were analysed through SEM imaging. Mapping analysis revealed that the primary elements of calcite were considerably more concentrated on the surface of bacterial concrete than in the control concrete.